A phylogenetic analysis of the wild Tulipa species (Liliaceae) of Kosovo based on plastid and nuclear DNA sequence. Issue 3 (16th September 2021) - Hajdari, Avni; Pulaj, Bledar; Schmiderer, Corinna; Malaj, Xhavit; Wilson, Brett; Lluga‐Rizani, Kimete; Mustafa, Behxhet
Abstract: In Kosovo, the genus Tulipa is represented by eight taxa, most of which form a species complex surrounding Tulipa scardica . To investigate the phylogenetic relationship of these Tulipa species a Bayesian analysis was undertaken using the ITS nuclear marker and trnL‐trnF, rbcL and psbA‐trnH plastid markers. The resulting phylogenetic trees show that Kosovarian Tulipa species consistently group into two main clades, the subgenera Eriostemones and Tulipa . Furthermore, our analyses provide some evidence that the subspecies of Tulipa sylvestris are genetically distinguishable, however not significantly enough to support their reclassification as species. In contrast, the markers provide some novel information to reassess the species concepts of the T . scardica complex. Our data provide support for the synonymisation of Tulipa luanica and Tulipa kosovarica under the species Tulipa serbica . Resolution and sampling limitations hinder any concrete conclusion about whether Tulipa albanica and T . scardica are true species, yet our data do provide some support that these are unique taxa and therefore should continue to be treated as such until further clarification. Overall, our work shows that genetic data will be important in determining species concepts in this genus, however, even with a molecular perspective pulling apart closely related taxa can be extremely challenging. Abstract :